KARAKTERISTIK TEKNOLOGI INFORMASI, BUDAYA ORGANISASI DAN KECOCOKAN INDIVIDU TERHADAP KINERJA KARYAWAN PT. JASA RAHARJA DI KALIMANTAN SELATAN - Anugraini, Mardiyah; Ngumar, Sutjipto; Suryono, Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2013)
The purpose of this research was to obtain empirical evidence whether the characteristics of information technology, organizational culture, individual match will have an influence on employee performance positih Public Agency State-owned enterprises (SOEs). The samples in this study were 37 employees of PT. Raharja Services in South Kalimantan. Data was collected through questionnaires to employees who deal directly with the use of information technology, organizational culture, and individual suitability. Analysis of this study using multiple regression analysis. The results showed that all three independent variables (information technology, organizational culture, and the fit people) have considerable influence on the dependent variable or performance. Effect of partial to the characteristics of information technology has a role in influencing employee performance optimally. Characteristics of organizational culture significantly influence employee performance. Which organizational culture that includes a group of friends easily cooperative and mutual trust, the system of administration of the company is always working in a procedural and structured. Compatibility of individuals have significant influence on employee performance effects. Which match individuals associated with knowing the purpose and mission of the company, working with computer technology, communication in the working relationship between ourselves and the consistent, able to use a computer better and the services provided by the system will be able to get both enhance employee performance when implemented with better. Keywords: Information Technology, Suitability Individual, Organizational Culture and Performance